2019
DOI: 10.1093/neuonc/noz166
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent glioblastoma versus late posttreatment changes: diagnostic accuracy of O-(2-[18F]fluoroethyl)-L-tyrosine positron emission tomography (18F-FET PET)

Abstract: Background Diagnostic accuracy in previous studies of O-(2-[18F]-fluoroethyl)-L-tyrosine (18F-FET) PET in patients with suspected recurrent glioma may be influenced by prolonged dynamic PET acquisitions, heterogeneous populations, different non–standard-of-care therapies, and PET scans performed at different time points post radiotherapy. We investigated the diagnostic accuracy of a 20-minute 18F-FET PET scan in MRI-suspected recurrent glioblastoma 6 months after standard radiotherapy and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…The same holds true when comparing the tumor uptake to that of inflammatory processes [ 11 ]. Previous studies specifically investigating the differentiation of TP and TRC in glioma [ 12 16 ] reported diagnostic accuracies of [ 18 F]FET PET between 81% [ 17 ] and 99% [ 18 ]. This considerable range could be attributed to the analysis of different PET parameters and the particular patient populations, varying in tumor subtypes and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The same holds true when comparing the tumor uptake to that of inflammatory processes [ 11 ]. Previous studies specifically investigating the differentiation of TP and TRC in glioma [ 12 16 ] reported diagnostic accuracies of [ 18 F]FET PET between 81% [ 17 ] and 99% [ 18 ]. This considerable range could be attributed to the analysis of different PET parameters and the particular patient populations, varying in tumor subtypes and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study suggests that increased uptake of 11 C-MET, such as 18 F-FDG, may have limited speci city in distinguishing in ammatory lesions from tumours [26]. Bashir et al [27] found that a 20-minute 18 F-FET PET scan is a powerful tool with TBRmax (sensitivity 99%, speci city 94%) to distinguish posttreatment changes from recurrent glioblastoma 6 months postradiotherapy. Bogsrud et al [28] reported the performance of a new type of amino acid 18 F-uciclovine in PET/CT of suspected residual or recurrent glioma, but the ability of 18 F-uciclovine PET/CT to discriminate between recurrent glioma and treatment-related changes could not be determined because no patients had con rmed treatment-related changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study suggests that increased uptake of 11 C-MET, such as 18 F-FDG, may have limited speci city in distinguishing in ammatory lesions from tumours[26]. Bashir et al [27] found that a 20-minute 18 F-FET PET scan is a powerful tool with TBRmax (sensitivity 99%, speci city 94%) to distinguish posttreatment changes from recurrent glioblastoma 6 months postradiotherapy. Bogsrud et al [28] reported the performance of a new type of amino acid 18 F-uciclovine in PET/CT of suspected residual or recurrent glioma, but the ability of 18 F-uciclovine PET/CT to discriminate between recurrent glioma and treatment-related changes could not be determined because no patients had con rmed treatment-related changes.…”
Section: Discussionmentioning
confidence: 99%